Toxin–Antitoxin systems: their role in persistence, biofilm formation, and pathogenicity. Issue 3 (24th February 2014) - Wen, Yurong; Behiels, Ester; Devreese, Bart
Abstract One of the most pertinent recent outcomes of molecular microbiology efforts to understand bacterial behavior is the discovery of a wide range of toxin–antitoxin (TA) systems that are tightly controlling bacterial persistence. While TA systems were originally linked to control over the genetic material, for example plasmid maintenance, it is now clear that they are involved in essential cellular processes like replication, gene expression, and cell wall synthesis. Toxin activity is induced stochastically or after environmental stimuli, resulting in silencing of the above‐mentioned biological processes and entry in a dormant state. In this minireview, we highlight the recent developments in research on these intriguing systems with a focus on their role in biofilms and in bacterial virulence. We discuss their potential as targets in antimicrobial drug discovery.